2012
DOI: 10.4103/0022-3859.93248
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of gabapentin for prevention of succinylcholine-induced fasciculation and myalgia

Abstract: Prophylactic use of gabapentin 600 mg in laparoscopic cholecystectomy decreases the incidence and severity of myalgia and fentanyl consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
4
20
0
Order By: Relevance
“…6 The exact mechanism is unknown, but several theories have been suggested. 5,7 Werawatganon et al 8 demonstrated that ECT patients who were treated with succinylcholine had increased serum myoglobin levels after the treatment, which was associated with muscle damage. 5,7 Werawatganon et al 8 demonstrated that ECT patients who were treated with succinylcholine had increased serum myoglobin levels after the treatment, which was associated with muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…6 The exact mechanism is unknown, but several theories have been suggested. 5,7 Werawatganon et al 8 demonstrated that ECT patients who were treated with succinylcholine had increased serum myoglobin levels after the treatment, which was associated with muscle damage. 5,7 Werawatganon et al 8 demonstrated that ECT patients who were treated with succinylcholine had increased serum myoglobin levels after the treatment, which was associated with muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment with diclofenac [1] , ketorolac [2] , calcium [3] , diazepam [4] , lignocaine [5] , magnesium [6] , small dose of succinylcholine as self-taming [7] , atracurium [8] , rocuronium [9] , cisatracurium [10] , remifentanyl [11] , gabapentin [12] , d-tubocurare [13] , pancuronium [14] , vecuronium [15] etc. have been tried to reduce or prevent succinylcholine induced fasciculations and myalgia but, none of them were thoroughly successful.…”
Section: Discussionmentioning
confidence: 99%
“…Succinylcholine, a depolarizing muscle relaxant with unique properties of rapid onset and short duration of action. 1 It also seems to be a popular muscle relaxant for ambulatory anesthesia and short surgical procedures. 2 It is regularly used by 69% of anesthesiologists and in 97% of emergency surgeries in Europe and the USA for adults.…”
Section: Introductionmentioning
confidence: 99%